2010
DOI: 10.1111/j.1460-9568.2010.07513.x
|View full text |Cite
|
Sign up to set email alerts
|

A synaptocentric view of the neuroendocrine response to stress

Abstract: The essential role of parvocellular neuroendocrine cells (PNCs) in the paraventricular nucleus of the hypothalamus (PVN) is to translate real or perceived challenges into a comprehensive glucocorticoid (GC) hormone response. Synaptic inputs encoding physical and psychological stress engage the hypothalamic-pituitary-adrenal axis (HPA) by increasing PNC activity, and corticotropin-releasing hormone production and release. Following robust recruitment in response to stress, GCs feedback to dampen PNC responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 159 publications
(148 reference statements)
1
32
0
Order By: Relevance
“…This stimulus-defined afferent ‘set’ then mediates a CRH neuronal response to the stressor that is appropriately graded to the nature and strength of the stimulus [Watts, 2005; Watts & Khan, 2011]. It will involve a controlled and coordinated activation of ACTH secretogogue synthesis and release processes, including increased action potential frequency, the accumulation of phospho-(p)CREB, nuclear TORC2, pERK1/2, Fos, CRH hnRNA and mRNA, ACTH secretogogue release, etc [Herman et al, 2003; Khan & Watts, 2004; Liu et al, 2008, 2010, 2012; Wamsteeker & Bains, 2010; Osterlund et al, 2012].…”
Section: Stressors Crh Neurons and The Hypothalamo-pituitary-adrmentioning
confidence: 99%
See 1 more Smart Citation
“…This stimulus-defined afferent ‘set’ then mediates a CRH neuronal response to the stressor that is appropriately graded to the nature and strength of the stimulus [Watts, 2005; Watts & Khan, 2011]. It will involve a controlled and coordinated activation of ACTH secretogogue synthesis and release processes, including increased action potential frequency, the accumulation of phospho-(p)CREB, nuclear TORC2, pERK1/2, Fos, CRH hnRNA and mRNA, ACTH secretogogue release, etc [Herman et al, 2003; Khan & Watts, 2004; Liu et al, 2008, 2010, 2012; Wamsteeker & Bains, 2010; Osterlund et al, 2012].…”
Section: Stressors Crh Neurons and The Hypothalamo-pituitary-adrmentioning
confidence: 99%
“…[see Herman et al, 2002, 2003; Levy & Tasker, 2012; Wamsteeker & Bains, 2010; Watts, 2005, for reviews]. So a fundamental part of understanding how CRH neuroendocrine control systems function is resolving how stressors impact CRH neurons using a pre-motor network that is comprised of the neurons that form direct synaptic connections with CRH neurons.…”
Section: A Pre-motor Network That Controls the Neuroendocrine Pvhmentioning
confidence: 99%
“…Parvocellular neuroendocrine cells in the paraventricular nucleus of the hypothalamus are at the head of the hypothalamic-pituitaryadrenal axis, both mediating glucocorticoid release and responding to negative feedback (Wamsteeker and Bains, 2010). Sustained stress unmasks presynaptic LTD GABA in which the probability of GABA release onto these neurons is decreased by retrograde opioid release (Wamsteeker Cusulin et al, 2013).…”
Section: Rgs4mentioning
confidence: 99%
“…Hewitt and colleagues (2009) demonstrated that following acute restraint stress, the parvocellular neuroendocrine cells undergo a depolarizing shift in the reversal potential for chloride ions by activation of α 1 -adrenoceptors thereby inhibiting the activity of transmembrane potassium-chloride-cotransporter 2. This impaired chloride ion extrusion within the parvocellular neuroendocrine cells leads to impaired GABA-A receptor-mediated inhibitory control of the HPA axis following the onset of stress (Wamsteeker and Bains, 2010). Under stressful conditions, the HPA axis is regulated by glucocorticoid-mediated negative feedback to extra-hypothalamic centres, hypothalamus, and anterior pituitary to terminate the stress response and restore homeostasis (Pardridge and Mietus, 1979;De Kloet et al, 1998).…”
Section: The Stress Systemsmentioning
confidence: 99%
“…The autonomic nervous system (ANS) quickly responds to stress exposure through the sympathetic and parasympathetic divisions. The rapidly activated sympathetic catecholamines are responsible for generation of the 'fight or flight' response in addition to potentiating the pituitary gland to subsequent hypothalamic activation (Wamsteeker and Bains, 2010). The hypothalamic-spinal-adrenocortical (HSA) axis modulates adrenal sensitivity to adrenocorticotropic hormone (ACTH) through a nitric oxide-mediated pathway (Jansen et al, 1995;Mohn et al, 2005;Ulrich-Lai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%